Analisis Pengendalian Kualitas Toples Kemasan Dengan Metode Taguchi Pada Pt.Xyz: Quality Control Analysis of Packaging Jars With Taguchi Method At Pt.Xyz - Ismail Ismail; Marwan Marwan (Engineering and Technology International Journal, 2022)
PT. XYZ is a company engaged in the plastic material industry, this company strives to continue to meet product quality by predetermined specifications. The company experienced problems in the production of defective products. The goal is to reduce the level of product defects in packaged jar products. The method used is the Taguchi method. The results of quality control show that there is a decrease in the resulting Quality Loss Function (QLF), which is Rp. 109. 308.492 / year to Rp. 25,259,040/year, so there is a decrease of Rp. 7,004,121 /month or Rp. 84,049,452 /year.